Complete Remission of Methotrexate-Related Epstein-Barr-Virus-Associated Hodgkin-Like Lymphoma following Withdrawal of MTX Coupled with Clarithromycin Administration - Nobuo Takemori; Hiroyuki Kaneko; Masaya Nakamura; Masaru Kojima (Case Reports in Hematology)
Patients with rheumatoid arthritis (RA) are known to develop lymphoproliferative disorders (LPDs) during the course of illness, particularly in cases treated with methotrexate (MTX) for long periods. We describe a case of MTX-related Epstein-Barr-virus-(EBV-) associated LPD resembling Hodgkin’s lymphoma (HL), in which a dramatic complete remission was achieved after withdrawal of MTX coupled with clarithromycin (CAM) administration. Withdrawal of MTX coupled with CAM administration seemed to be effective for treating MTX-related EBV-associated LPDs. In particular, an immunomodulative effect of CAM might have been involved in achieving complete remission.